Metabolic Interplay between the Immune System and Melanoma Cells: Therapeutic Implications - Indini, Alice (Biomedicines, 2021)
Malignant melanoma represents the most fatal skin cancer due to its aggressive biological behavior and high metastatic potential. Treatment strategies for advanced disease have dramatically changed over the last years due to the introduction of BRAF/MEK inhibitors and immunotherapy. However, many patients either display primary (i.e., innate) or eventually develop secondary (i.e., acquired) resistance to systemic treatments. Treatment resistance depends on multiple mechanisms driven by a set of rewiring processes, which involve cancer metabolism, epigenetic, gene expression, and interactions within the tumor microenvironment. Prognostic and predictive biomarkers are needed to guide patients’ selection and treatment decisions. Indeed, there are no recognized clinical or biological characteristics that identify which patients will benefit more from available treatments, but several biomarkers have been studied with promising preliminary results. In this review, we will summarize novel tumor metabolic pathways and tumor-host metabolic crosstalk mechanisms leading to melanoma progression and drug resistance, with an overview on their translational potential as novel therapeutic targets.